2017
DOI: 10.1051/0004-6361/201630034
|View full text |Cite
|
Sign up to set email alerts
|

From molecules to young stellar clusters: the star formation cycle across the disk of M 33

Abstract: Aims. We study the association between Giant Molecular Clouds (GMCs) and Young Stellar Cluster Candidates (YSCCs), to shed light on the time evolution of local star formation episodes in the nearby galaxy M33. Methods. The CO (J=2-1) IRAM-all-disk survey was used to identify and classify 566 GMCs with masses between 2×10 4 and 2×10 6 M across the whole star forming disk of M33. In the same area, there are 630 YSCCs, identified using Spitzer-24 µm data. Some YSCCs are embedded star-forming sites while the major… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
190
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(231 citation statements)
references
References 41 publications
(90 reference statements)
41
190
0
Order By: Relevance
“…If these regional variations arise from individual GMCs, the H I-CO line widths may indicate changes in the local environment or the evolutionary state of the cloud. If the latter is true, the lack of a radial trend is consistent with the radial distribution of cloud evolution types from Corbelli et al (2017), which are well-mixed in the inner 6 kpc (see also Gratier et al 2012).…”
Section: Regional Variations In the H I-co Line Widthssupporting
confidence: 65%
“…If these regional variations arise from individual GMCs, the H I-CO line widths may indicate changes in the local environment or the evolutionary state of the cloud. If the latter is true, the lack of a radial trend is consistent with the radial distribution of cloud evolution types from Corbelli et al (2017), which are well-mixed in the inner 6 kpc (see also Gratier et al 2012).…”
Section: Regional Variations In the H I-co Line Widthssupporting
confidence: 65%
“…Other studies, most of which rely on different methodological approaches, have also found evidence that GMCs are dispersed within a few Myr after the onset of massive star formation (e.g. Kawamura et al 2009;Whitmore et al 2014;Hollyhead et al 2015;Corbelli et al 2017;Grasha et al 2019;Hannon et al 2019;Hygate et al 2019a). A detailed comparison between the measured feedback time-scales and theoretical expectations for different feedback mechanisms is investigated in more detail in a companion paper (M. Chevance et al in prep.).…”
Section: Feedback Time-scalementioning
confidence: 96%
“…If Ω = 0.1 km s −1 pc −1 is an appropriate gradient, then the rotation period is T = 2π/Ω = 61 Myr. Even allowing for projection effects and the correction below, the rotation period is greater than typical GMC lifetimes of ∼ 15Myr (e.g., Corbelli et al 2017). Figure 4 shows the specific angular momenta of the clouds as a histogram.…”
Section: Rotational Versus Binding Energymentioning
confidence: 99%